The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019 International Conference on Robotics and Automation (ICRA) 2019
DOI: 10.1109/icra.2019.8793592
|View full text |Cite
|
Sign up to set email alerts
|

Development of SAM: cable-Suspended Aerial Manipulator

Abstract: High risk of a collision between rotor blades and the obstacles in a complex environment imposes restrictions on the aerial manipulators. To solve this issue, a novel system cable-Suspended Aerial Manipulator (SAM) is presented in this paper. Instead of attaching a robotic manipulator directly to an aerial carrier, it is mounted on an active platform which is suspended on the carrier by means of a cable. As a result, higher safety can be achieved because the aerial carrier can keep a distance from the obstacle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 23 publications
0
70
0
Order By: Relevance
“…In order to tackle this issue, Fig. 1: DLR Suspended Aerial Manipulator [13], whose model was used to validate the proposed approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to tackle this issue, Fig. 1: DLR Suspended Aerial Manipulator [13], whose model was used to validate the proposed approach.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that, if the gains are kept within a given range and if allowed by the passivity condition, the presented method is able to successfully reduce the accumulated drift caused by admittance type passivity controllers (PCs) in TDPA. In addition to hardware experiments with commercially available Novint Falcon haptic devices, teleoperation of the dynamic model of a Suspended Aerial Manipulator [13] (see Fig. 1) is simulated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the DLR Suspended Aerial Manipulator (SAM) [44] was chosen as the slave robot. It consists of an omnidirectional octarotor platform, which hangs from a carrier by means of cables.…”
Section: Methodsmentioning
confidence: 99%
“…Within the class of aerial manipulators, those presenting kinematic redundancy like the DLR Suspended Aerial Manipulator (SAM; Sarkisov et al, 2019; see Figure 14) are able to allow the user to not only control the robotic arm, but also steer the UAV (also called flying base) to achieve a desired camera view of the task being performed. Nevertheless, two main issues arise in that application.…”
Section: Aerial Manipulation (Hierarchical Bilateral Teleoperation and Haptic Augmentation)mentioning
confidence: 99%